Integral honeycomb type non-noble metal catalyst as well as preparation method and application thereof
By preparing an integral honeycomb non-precious metal catalyst, the problems of high catalyst cost, poor reusability and poor sulfur resistance in the prior art are solved, and the effective treatment of alkali residue waste liquid is achieved, COD is reduced and maintained Long-term stable catalytic performance.
Patent Information
- Application Number
- CN202411303667.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2024-12-13
AI Technical Summary
When treating the alkali residue waste liquid, existing catalysts have problems such as high preparation cost, poor reusability, complex catalyst preparation process, high catalytic reaction conditions and poor sulfur resistance, making it difficult to effectively reduce COD in the alkali residue.
Using a whole honeycomb non-precious metal catalyst, the preparation method is to mix silica, alumina, nanoactive oxides and adhesives in a certain proportion, stir and mold into a honeycomb mud tire, let stand and air-dry and roast, and make a relatively expensive A catalyst with low sulfur resistance.
It has achieved effective reduction of alkali slag COD, the catalytic reaction conditions are mild, the catalyst is cheap and easy to disassemble, has good water and sulfur resistance, and can maintain long-term stable activity in a high sulfide environment.
Smart Images

Figure CN119114047A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalysts, and in particular to an integral honeycomb type non-precious metal catalyst and a preparation method and application thereof. Background Art
[0002] In the petrochemical industry, the waste alkali liquid produced after washing catalytic cracking gasoline, liquid hydrocarbons in gas separation units, etc. with alkali liquid is collectively called alkali residue. It contains a large amount of toxic and harmful substances such as neutral oil, organic acid, volatile phenol and sulfide. The wastewater is dark brown and has a foul odor. The COD is as high as hundreds of thousands. It is extremely difficult to treat and has always been a problem that has plagued oil refining companies.
[0003] At present, the most mainstream method for alkaline slag treatment is wet oxidation, which operates under high temperature (120-320°C) and high pressure (0.5-20MPa) conditions, using gaseous oxygen as an oxidant to oxidize and decompose organic matter in water into small molecular organic or inorganic matter. This method has the characteristics of no secondary pollution and low treatment cost. However, traditional wet oxidation requires higher temperature and pressure and a relatively long residence time, high requirements for equipment materials, large one-time investment, and wet oxidation can only be used as pretreatment, and its effluent also has a high COD. In order to reduce the temperature and pressure required for the reaction and improve the treatment effect, wet catalytic oxygen treatment technology (Catalytic wet air oxidation, referred to as CWAO) has become a research hotspot in recent years. However, for catalytic wet oxidation technology, the preparation of efficient catalysts is the core of its technology.
[0004] Wet oxidation catalysts can be divided into homogeneous catalysts and heterogeneous catalysts. The former has higher catalytic activity, but the catalyst is difficult to analyze from the system, cannot be reused and easily causes secondary pollution, so it is less used, while the latter has the advantages of easy separation and reusability, so it is widely used. At present, heterogeneous catalysts are mainly precious metal catalysts with platinum, palladium, rhodium, iridium, and ruthenium as active components, such as the catalysts involved in patents CN107442148A, CN107442115B, and CN107442116A. Precious metal catalysts have superior performance, high catalytic activity, and strong acid and alkali resistance, but they are expensive and very limited in use.
[0005] Chinese patent CN1876232A discloses an activated carbon-supported copper oxide catalyst and its preparation method, which uses activated carbon-supported copper oxide as a catalyst and H2O2 to catalytically oxidize and treat coking wastewater. The copper oxide catalyst prepared by the patent method, in the application of reducing wastewater COD, must add 0.5-1.0mL 30% H2O2 for every 100ml COD of 1000mg / L wastewater to achieve a more significant effect of reducing COD, and the use cost is high and the safety is low. Chinese patent CN103157501A discloses a preparation method of a catalyst for catalytic wet oxidation of organic pollutants in water, which uses SBA-15 molecular sieve as a carrier and CuO as an active component as a catalyst to catalytically oxidize organic matter in water. The COD in the wastewater treated by this patent can only reach 200mg / L at most, and the organic matter in the wastewater is phenol-type organic matter that is easier to oxidize and decompose, and the use limitations are more obvious.
[0006] Chinese patent CN103157493A discloses a composite functional nanosphere catalyst with a recyclable function loaded with precious metals and its application in catalyzing the reduction of p-nitrophenol, wherein precious metal nanoparticles and magnetic nanoparticles are coated in a polymer to obtain a composite functional nanosphere catalyst loaded with precious metals in a polar solvent. The catalyst is loaded with precious metals such as gold, silver, and palladium, which is not only expensive to prepare, but also the precious metals are very easy to form sulfates with sulfides, thereby losing catalytic activity, and the actual application effect of the catalyst cannot be guaranteed.
[0007] In summary, the catalysts used in the prior art have the disadvantages of extremely high preparation cost, poor reusability, complex catalyst preparation process, high catalytic reaction conditions, and poor catalyst sulfur resistance. Therefore, it is necessary to develop a non-precious metal heterogeneous honeycomb monolithic catalyst with low price, high sulfur resistance, simple preparation process, mild catalytic reaction conditions, easy disassembly and good effect on reducing COD of alkali slag. Summary of the invention
[0008] The object of the present invention is to provide an integral honeycomb non-precious metal catalyst and a preparation method and application thereof.
[0009] The technical solution adopted by the present invention is:
[0010] A method for preparing an integral honeycomb non-precious metal catalyst comprises the following steps:
[0011] 1) Mixing silicon dioxide, aluminum oxide, nano-active oxide and adhesive in a certain proportion to prepare a catalyst base material;
[0012] 2) adding a certain amount of water to the catalyst base material, stirring and kneading, and extruding to form a honeycomb clay mold;
[0013] 3) placing the honeycomb clay obtained in step 2) in an air-dried state, and then drying it to obtain a semi-finished catalyst product;
[0014] 4) calcining the semi-finished catalyst to obtain a finished catalyst.
[0015] As a further improvement of the present invention, in step 1), the nano-active oxide is preferably at least one of zinc oxide, iron oxide, zirconium oxide and cerium oxide, and more preferably the nano-active oxide is zinc oxide; the adhesive is preferably selected from at least one of water glass, glucose and glycerol, and more preferably the adhesive is a mixture of glucose and glycerol.
[0016] As a further improvement of the present invention, in step 1), preferably, the silicon oxide and aluminum oxide independently have a particle size of 1 to 100 μm, and more preferably, the particle size of the silicon oxide and aluminum oxide is 5 to 20 μm; preferably, the nano-active oxide has a particle size of 0.1 to 1 μm, and more preferably, the particle size of the nano-active oxide is 0.1 to 0.3 μm.
[0017] As a further improvement of the present invention, in step 1), based on the total weight of the catalyst base material, the content of the nano active oxide is preferably 1 to 50%, more preferably 5 to 25%; the content of the silicon oxide is 10 to 80%, more preferably 30 to 60%; the content of the aluminum oxide is 10 to 70%, more preferably 30 to 60%; the content of the adhesive is 1 to 30%, more preferably 5 to 15%.
[0018] As a further improvement of the present invention, in step 1), in step 2), the amount of water added is preferably 10 to 100%, more preferably 30 to 60%, relative to the weight of the catalyst base material.
[0019] As a further improvement of the present invention, in step 2), the extrusion pressure is 1 to 300 MPa, more preferably 20 to 100 MPa.
[0020] As a further improvement of the present invention, in step 3), preferably, the air-drying is carried out at 0 to 35°C, more preferably at room temperature; the air-drying time is 0.5 to 80 hours, more preferably 2 to 48 hours; the drying temperature is 60 to 400°C, more preferably 100 to 200°C; the drying time is 0.5 to 20 hours, more preferably 1 to 12 hours. Drying can be carried out by any commonly used drying equipment in the field of catalyst preparation, such as an oven, a hot air furnace or a track kiln.
[0021] As a further improvement of the present invention, in step 4), the calcination temperature is preferably 200-900° C., more preferably 400-600° C.; the calcination time is 1-200 h, more preferably 2-48 h.
[0022] The present invention also provides a catalyst prepared according to any one of the above preparation methods, wherein the mesh number of the catalyst is 100 mesh, 200 mesh, 300 mesh, 400 mesh or 500 mesh, preferably the mesh number is 200 mesh, 300 mesh or 400 mesh; the size of the catalyst is 150mm×150mm×50mm, 150mm×150mm×100mm, 150mm×150mm×150mm, 100mm×100mm×50mm, 100mm×100mm×100mm or 100mm×100mm×150mm.
[0023] The present invention also provides an application of the catalyst in treating alkali residue waste liquid.
[0024] Beneficial effects of the invention: The preparation method of the catalyst of the present invention has a simple process and can obtain a honeycomb integral catalyst through one-step molding. The obtained catalyst has a low price and is easy to disassemble. The catalytic reaction conditions are mild, the effect of reducing the COD of alkali residue is good, the sulfur resistance is high, and it has good water resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is the flow chart of the catalyst performance evaluation device. DETAILED DESCRIPTION
[0026] The present application will be further described in detail below through specific implementation methods. It should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application, but do not limit the present invention in any way.
[0027] Any specific numerical value disclosed herein (including the endpoint of the numerical range) is not limited to the exact value of the numerical value, but should be understood to also cover values close to the exact value, such as all possible numerical values within the range of ±5% of the exact value. In addition, for the disclosed numerical range, the endpoint values of the range, the endpoint values and the specific point values in the range, and the specific point values can be arbitrarily combined to obtain one or more new numerical ranges, and these new numerical ranges should also be regarded as specifically disclosed herein.
[0028] Unless otherwise specified, the terms used herein have the same meaning as commonly understood by those skilled in the art. If a term is defined herein and its definition is different from the commonly understood meaning in the art, the definition herein shall prevail.
[0029] The expressions "comprising" or "including" herein should be interpreted as including all the specifically mentioned features as well as optional, additional, unspecified features. As used herein, the use of the term "comprising" also discloses solutions in which there are no further features than the specifically mentioned features, such as the expressions "consisting essentially of" and "consisting of".
[0030] The present invention is further described in detail below using examples, but the present invention is not limited to these examples.
[0031] The raw materials used in the following examples and comparative examples are all commercially available.
[0032] Example 1
[0033] 1) 400 g of aluminum oxide (D90 = 10 μm), 400 g of silicon oxide (D90 = 10 μm), 400 g of zinc oxide (D90 = 0.2 μm), 200 g of glucose, and 200 g of glycerol were mixed, and then dry-stirred until the mixture was uniformly mixed;
[0034] 2) Add 800g of water to the above dry powder;
[0035] 3) Mechanical kneading is performed until a plasticine-like clay is formed;
[0036] 4) Extruding the above-mentioned clay mold with a die at an extrusion pressure of 20 MPa to obtain a wet honeycomb catalyst molded body with a honeycomb specification of 100 mm×100 mm×50 mm and a hole number of 200 meshes;
[0037] 5) The catalyst semi-finished product obtained in step 4) is air-dried for 12 hours, and then dried at a temperature of 150° C. for 4 hours to obtain a dried honeycomb catalyst semi-finished product;
[0038] 6) The catalyst semi-finished product obtained in step 5) was calcined at 500° C. for 4 h to obtain a catalyst finished product 1, wherein the catalyst active component is highly dispersed nano zinc oxide (233 g / L honeycomb catalyst finished product), numbered 1-1.
[0039] Example 2
[0040] 1) 400 g of aluminum oxide (D90=10 μm), 400 g of silicon oxide (D90=10 μm), 100 g of zinc oxide (D90=0.2 μm), 100 g of iron oxide (D90=0.2 μm), 100 g of zirconium oxide (D90=0.2 μm), 100 g of cerium oxide (D90=0.2 μm), 200 g of glucose, and 200 g of glycerol were mixed, and then dry-stirred until the mixture was uniformly mixed;
[0041] 2) Add 800g of water to the above dry powder;
[0042] 3) Mechanical kneading is performed until a plasticine-like clay is formed;
[0043] 4) Extruding the above-mentioned clay mold with a die at an extrusion pressure of 20 MPa to obtain a wet honeycomb catalyst molded body with a honeycomb specification of 100 mm×100 mm×50 mm and a hole number of 200 meshes;
[0044] 5) The catalyst semi-finished product obtained in step 4) is air-dried for 12 hours, and then dried at a temperature of 150° C. for 4 hours to obtain a dried honeycomb catalyst semi-finished product;
[0045] 6) The catalyst semi-finished product obtained in step 5) is calcined at 500°C for 4 hours to obtain a catalyst finished product 1, wherein the catalyst active components are highly dispersed nano zinc oxide (58g / L honeycomb catalyst finished product), nano iron oxide (58g / L honeycomb catalyst finished product), nano zirconium oxide (58g / L honeycomb catalyst finished product) and nano cerium oxide (58g / L honeycomb catalyst finished product), numbered 1-2.
[0046] Example 3
[0047] 1) 400 g of aluminum oxide (D90 = 1 μm), 400 g of silicon oxide (D90 = 1 μm), 50 g of zinc oxide (D90 = 0.1 μm), 75 g of glucose, and 75 g of glycerol were mixed, and then dry-stirred until the mixture was uniform;
[0048] 2) Add 1000g of water to the above dry powder;
[0049] 3) Mechanical kneading is performed until a plasticine-like clay is formed;
[0050] 4) Extruding the above-mentioned clay mold with a die at an extrusion pressure of 20 MPa to obtain a wet honeycomb catalyst molded body with a honeycomb specification of 100 mm×100 mm×50 mm and a hole number of 200 meshes;
[0051] 5) The catalyst semi-finished product obtained in step 4) is air-dried for 12 hours, and then dried at a temperature of 150° C. for 4 hours to obtain a dried honeycomb catalyst semi-finished product;
[0052] 6) The catalyst semi-finished product obtained in step 5) was calcined at 500° C. for 4 h to obtain a catalyst finished product 1, wherein the catalyst active component is highly dispersed nano zinc oxide (38 g / L honeycomb catalyst finished product), numbered 1-3.
[0053] Example 4
[0054] 1) 400 g of aluminum oxide (D90 = 100 μm), 400 g of silicon oxide (D90 = 100 μm), 200 g of zinc oxide (D90 = 1 μm), 200 g of glucose, and 200 g of glycerol were mixed, and then dry-stirred until the mixture was uniform;
[0055] 2) Add 420 g of water to the above dry powder;
[0056] 3) Mechanical kneading is performed until a plasticine-like clay is formed;
[0057] 4) Extruding the clay mold through a mold at an extrusion pressure of 100 MPa to obtain a wet honeycomb catalyst molded body with a honeycomb size of 100 mm×100 mm×50 mm and a hole number of 200 meshes;
[0058] 5) The catalyst semi-finished product obtained in step 4) is air-dried for 80 hours, and then dried at a temperature of 200° C. for 12 hours to obtain a dried honeycomb catalyst semi-finished product;
[0059] 6) The catalyst semi-finished product obtained in step 5) is calcined at 600° C. for 48 hours to obtain a catalyst finished product 1, wherein the catalyst active component is highly dispersed nano zinc oxide (140 g / L honeycomb catalyst finished product), numbered 1-4.
[0060] Comparative Example
[0061] As Comparative Example 1, nano-sized copper oxide (D90=0.2 μm) was used to replace the nano-sized zinc oxide used in Example 1.
[0062] As Comparative Example 2, ordinary zinc oxide (D90=10 μm) was used to replace the nano-grade zinc oxide used in Example 4.
[0063] Comparative Example 1
[0064] 1) 400 g of aluminum oxide (D90 = 10 μm), 400 g of silicon oxide (D90 = 10 μm), 400 g of copper oxide (D90 = 0.2 μm), 200 g of glucose, and 200 g of glycerol were mixed, and then dry-stirred until the mixture was uniform;
[0065] 2) Add 800g of water to the above dry powder;
[0066] 3) Mechanical kneading is performed until a plasticine-like clay is formed;
[0067] 4) Extruding the above-mentioned clay mold with a die at an extrusion pressure of 20 MPa to obtain a wet honeycomb catalyst molded body with a honeycomb specification of 100 mm×100 mm×50 mm and a hole number of 200 meshes;
[0068] 5) The catalyst semi-finished product obtained in step 4) is air-dried for 12 hours, and then dried at a temperature of 150° C. for 4 hours to obtain a dried honeycomb catalyst semi-finished product;
[0069] 6) The catalyst semi-finished product obtained in step 5) was calcined at 500° C. for 4 h to obtain a catalyst finished product 1, wherein the catalyst active component is highly dispersed nano-copper oxide (233 g / L honeycomb catalyst finished product), numbered 2-1.
[0070] Comparative Example 2
[0071] 1) 400 g of aluminum oxide (D90 = 10 μm), 400 g of silicon oxide (D90 = 10 μm), 200 g of zinc oxide (D90 = 10 μm), 200 g of glucose, and 200 g of glycerol were mixed, and then dry-stirred until the mixture was uniform;
[0072] 2) Add 420 g of water to the above dry powder;
[0073] 3) Mechanical kneading is performed until a plasticine-like clay is formed;
[0074] 4) Extruding the clay mold through a mold at an extrusion pressure of 100 MPa to obtain a wet honeycomb catalyst molded body with a honeycomb size of 100 mm×100 mm×50 mm and a hole number of 200 meshes;
[0075] 5) The catalyst semi-finished product obtained in step 4) is air-dried for 80 hours, and then dried at a temperature of 200° C. for 12 hours to obtain a dried honeycomb catalyst semi-finished product;
[0076] 6) The catalyst semi-finished product obtained in step 5) is calcined at 600° C. for 48 hours to obtain catalyst 1, wherein the catalyst active component is zinc oxide (140 g / L honeycomb catalyst finished product), numbered 2-2.
[0077] The catalysts prepared in Examples 1-4 and Comparative Examples 1-2 were used in the wet oxidation experiment of oil refining waste alkali residue. The experimental flow chart is as follows: Figure 1 As shown in the figure, under high temperature and high pressure, the oil refinery waste alkali slag with a COD of 100000 mg / L (including sulfide content of 50000 mg / L) is continuously pumped into a reactor equipped with a catalyst, and high-pressure oxygen-containing gas (air) is introduced at the same time. The organic matter and sulfur-containing compounds in the oil refinery waste alkali slag are degraded into CO2, H2O and SO4 under the action of the catalyst and oxygen. 2- The COD value of the liquid at the reactor outlet was tested after continuous flow for 1h, 12h, 24h, 48h, 96h, 192h and 384h. The results are shown in Table 1.
[0078] Evaluation conditions: temperature 200°C, pressure 0.3MPaG, catalyst loading 0.5L, waste alkali liquid flow 1.5L / h, air flow 0.5Nm 3 / h.
[0079] Table 1 Catalyst performance evaluation results of Example catalysts 1-1 to 1-4 and Comparative Example catalysts 2-1 and 2-2
[0080]
[0081] It can be seen from Table 1 that the catalysts 1-1 to 1-4 prepared by the method of the present invention have COD≤5000mg / L after treating the alkali residue wastewater, and can be directly subjected to biochemical treatment later. However, the catalysts 2-1 and 2-2 not prepared by the present method have COD>5000mg / L after treating the alkali residue wastewater, and cannot be directly subjected to biochemical treatment later. At the same time, the catalysts prepared by the method of the present invention can maintain long-term stability in performance under extremely high sulfide content. However, the catalysts not prepared by the present invention have rapidly decayed activity under extremely high sulfide content.
Claims
1. A method for preparing a monolithic honeycomb non-precious metal catalyst, It is characterized in that The steps include: 1) Mixing silicon dioxide, aluminum oxide, nano-active oxide and adhesive in a certain proportion to prepare a catalyst base material; 2) adding a certain amount of water to the catalyst base material, stirring and kneading, and extruding to form a honeycomb clay mold; 3) placing the honeycomb clay obtained in step 2) in an air-dried state, and then drying it to obtain a semi-finished catalyst product; 4) calcining the semi-finished catalyst to obtain a finished catalyst.
2. The preparation method according to claim 1, It is characterized in that In step 1), the nano active oxide is at least one of zinc oxide, iron oxide, zirconium oxide and cerium oxide; the adhesive is at least one of water glass, glucose and glycerol.
3. The preparation method according to claim 2, It is characterized in that In step 1), the silicon oxide and the aluminum oxide independently have a particle size of 1 to 100 μm, and the nano active oxide has a particle size of 0.1 to 1 μm.
4. The preparation method according to claim 1, It is characterized in that In step 1), based on the total weight of the catalyst base material, the content of the nano active oxide is 1-50%, the content of the silicon oxide is 10-80%, the content of the aluminum oxide is 10-70%, and the content of the adhesive is 1-30%.
5. The preparation method according to claim 1, It is characterized in that In step 2), the amount of water added is 10-100% relative to the weight of the catalyst base material.
6. The preparation method according to claim 1, It is characterized in that In step 2), the extrusion pressure is 1 to 300 MPa.
7. The preparation method according to claim 1, It is characterized in that In step 3), the static air drying is carried out at 0-35° C. for 0.5-80 h; the drying temperature is 60-400° C. for 0.5-20 h.
8. The preparation method according to claim 1, It is characterized in that In step 4), the calcination temperature is 200-900° C. and the calcination time is 1-200 hours.
9. The catalyst obtained according to the preparation method according to any one of claims 1 to 8, having a mesh size of 100 mesh, 200 mesh, 300 mesh, 400 mesh or 500 mesh, and a size of 150mm×150mm×50mm, 150mm×150mm×100mm, 150mm×150mm×150mm, 100mm×100mm×50mm, 100mm×100mm×100mm or 100mm×100mm×150mm.
10. Use of the catalyst according to claim 9 in treating alkali residue waste liquid.
